Synergy Between Dietary Quercetin and Vitamin E Supplementation in Aged Hen’s Diet Improves Hatching Traits, Embryo Quality, and Antioxidant Capacity of Chicks Hatched From Eggs Subjected to Prolonged Storage - Amevor, Felix Kwame; Cui, Zhifu; Du, Xiaxia; Ning, Zifan; Deng, Xun; Xu, Dan; Wu, Youhao; Cao, Xueqing; Wei, Shuo; Shu, Gang; Han, Xue; Tian, Yaofu; et al. (Frontiers in Physiology, 2022)
The current study aims to investigate the effects of the synergy between quercetin and vitamin E in aged hen’s diet on hatchability and antioxidant levels of the embryo and newly hatched chicks from prolonged storage eggs. A total of 400 breeder laying hens of 65 weeks of age were selected and randomly divided into 4 groups. Birds were fed a basal diet alone (Control), and basal diets supplemented with quercetin (Q) (0.4 g/kg) and vitamin E (VE) (0.2 g/kg) alone and their combination (0.4g/kg Q + 0.2g/kg VE) for 14 weeks, respectively, to determine their effects on yolk antioxidant status, fertility, embryonic mortality, hatchability, antioxidant status of embryonic tissues, as well as the antioxidant status of the newly hatched chicks. The results showed that the hen’s dietary Q + VE increased the yolk weight, as well as increased the antioxidant status of the egg yolk (P < 0.05). Compared with the control group, the supplementation of Q + VE significantly increased the hatchability of set-fertile eggs and decreased early embryonic mortality in eggs stored for 7 and 14 days, respectively (P < 0.05), and also improved the antioxidant capacity of the embryos obtained from eggs stored for 14 days (before incubation) (P < 0.05). Moreover, Q + VE increased the levels of SOD, GSH-Px, T-AOC, T-SOD, and CAT in the liver, heart, and pectoral muscle of the embryo, 1-day-old and 14-day-old chicks (P < 0.05), as well as upregulated the antioxidant related genes (GPx-1, GPx-2, GPx-4, DIO-1, and SOD-1) in the liver of the embryo, 1-day-old and 14-day-old chicks hatched from 14-days storage eggs (P < 0.05). Meanwhile, the MDA levels were decreased by the Q + VE in the embryo and post-hatched chicks (P < 0.05). In conclusion, these findings suggested that maternal dietary Q + VE exerts beneficial synergistic effects on the antioxidant capacity of the egg yolk, embryo, and chicks during prolong egg storage, therefore, Q + VE could be used as a dietary measure to enhance hatchability and chick quality in poultry production.